Pernicious Anemia in an Adult with Trisomy 21 - Kentaro Kamada; Osamu Kawano; Satoshi Yakuwa; Kentaro Wakasa; Kimiaki Uetake (Case Reports in Immunology)
Pernicious anemia is an autoimmune disease caused by the malabsorption of vitamin B12. It usually appears in the elderly. People with trisomy 21 are susceptible to autoimmune diseases. This susceptibility is thought to be due to altered expression of the AIRE gene, which is located in the 21q22.3 region. Although pernicious anemia is not common in people with trisomy 21, AIRE is pointed out as a susceptibility gene of pernicious anemia in a genome-wide association study. Here, we report a man with trisomy 21, who suffered from the pernicious anemia. When he was in his 30 s, he visited our hospital because of diarrhea and poor oral intake. He showed thrombocytopenic purpura-like features, and was diagnosed as pernicious anemia. After supplementation of vitamin B12, he recovered from the illness. The reason for his early onset may be because of trisomy 21. Altered expression of AIRE might trigger the disease.